Board diversity effect on financial performance in Indonesian financial institution - Sani Kurniawan, Muhammad; Dwi Hardiman, Hendi; Santoso, Agus; Kurniawati, Renny (Edelweiss Applied Science and Technology, 2024)
Board diversity is important in the current business environment, board diversity considered be able to provide diverse points of view, it is considered to be able to build effective corporate governance. This study highlights board diversity issue in Indonesia financial sector institution, taking consideration their effect on financial performance measured using Tobin Q. This study purpose are analyses the effect of board of commissioners gender diversity, board of directors gender diversity, board of commissioners nationality diversity, and board of directors nationality diversity on financial performance. The investigation makes use of regression analysis from 67 financial institution listed in Indonesia from 2020 until 2022, with total 201 sample. Our finding highlights that board of directors gender diversity, and board of directors nationality diversity positively affects financial performance, while board of commissioners nationality diversity negatively affects financial performance, and board of commissioners gender diversity does not affect financial performance.